Application of Unmanned Aerial Vehicle (UAV) in Terrain Mapping: Systematic Literature Review - Nordin, Zieziyana; Mohd Salleh, Anuar (International Journal of Sustainable Construction Engineering and Technology, 2022)
Unmanned Aerial Vehicle (UAV) is an advanced technology that can be control remotely. It hovers up in the air and travel with different height and distance depending on the capability of the UAV. Originally, this technology was invented for military practice. Now, the innovation of UAV is growing and have contribute to various field including terrain mapping in surveying work. Carrying out mapping task in terrain such as mountain, valley, plateau, or rainforest can be a difficult task in-terms of time, practicality and cost. Another challenge is when the survey area is permanently clouded over and the limited availability of aircraft platforms and the orbit features of satellites causing difficulties to obtain high quality photos. Therefore, there are much research that used UAV technology to do mapping work and obtain Digital Terrain Model (DTM), Digital Surface Model (DSM) and Digital Elevation Model for various purposes. In this study, systematic literature review using thematic analysis methodology was used to review, evaluate and combine relevant literature review. The aim of this study is to categorise the application for terrain mapping using UAV and also to identify the system and result improvement of UAV during the usage in terrain mapping. From the thematic analysis, two themes which are understanding the earth structure with the subtheme of geotechnical study, geomorphological study and flood study and UAV system improvement with the subtheme of accuracy assessment, accuracy enhancement and resolution were formed.